Encyclopedia of landscape design planning, building, and planting your perfect outdoor space - Young, Chris 1976- (DK Publishing, 2017)
Offers advice, techniques, and instructions on the process of designing a home garden, including layouts, illustrated listings of plants, and simple construction projects.--Source other than Library of Congress.